Analysis of Discipline Character and Learning Interest on Student Learning Outcomes - Kartika Himmatu ‘Adila; Susanto, Susanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study was motivated by the decline in student learning outcomes in the odd semester of the 2022/2023 school year which was caused by students paying less attention to the explanation and material from the teacher during the learning process. Such as not doing assignments on time, often chatting alone when the teacher explains, lack of interest in learning, and there are some children who have low learning outcomes. Therefore, it is necessary to instill discipline in learning since childhood, because it will help children control themselves in the formation of self-awareness in learning without an element of compulsion. This study aims to determine the relationship between learning discipline and students' interest in learning. The research method used is a quantitative method with a correlational approach that uses ex post facto research. The sample in the study was class III students with a total of 14 people, whose sampling used the saturated sample method because all students in class III were sampled in the study. Data collection was carried out using questionnaire and documentation techniques. The results showed that: 1) There is a significant relationship between learning discipline and student learning outcomes with a Thitung value of 8.131. 2) There is a significant relationship between learning discipline and student learning outcomes with a Thitung of 3.459. 3). There is a significant relationship simultaneously between learning discipline and learning interest on student learning outcomes with a T-count of 6.698.